Ethnobotanic study in sapi sonok madura herbal as a science learning resource for junior high school students - Ainunnuril Amelia; Mochammad Yasir; Rahmad Fajar Sidik (Universitas PGRI Pontianak, 2024)
The lack of contextual learning in the field of science is one of the constraints in teaching and learning science. Contextual learning can be achieved by integrating local wisdom from the students' surroundings into science lesson plans. This approach serves as a bridge for introducing and preserving local wisdom by making it familiar to students. Through science learning based on contextual approaches, students can easily find real-life examples of scientific concepts that they study and observe in their daily lives. This research aims to describe the study of ethnobotany, or the types of natural materials found in one of Madura's local wisdom traditions, specifically the Madura Sonok cow herbal medicine. The findings of this study show a correlation between indigenous knowledge and scientific knowledge. The local community's knowledge of utilizing specific natural materials for livestock consumption, believed to have specific properties and benefits, is connected to scientific concepts in the study of natural materials or their classification. There are many types of scientific concepts that can be integrated with ethnobotany in the context of Madura Sonok cow herbal medicine, such as topics related to temperature and heat, elements, compounds, and mixtures, as well as the classification of living organisms. The method used in this study is a descriptive qualitative approach with data collection techniques based on field data (interviews with key informants) and supported by relevant articles. The data analysis employed in this study is inductive analysis. This research was conducted in the area known for the local wisdom of Sonok cows, specifically in West Waru, Pamekasan. The conclusion of this study is that the process of making Madura Sonok cow herbal medicine demonstrates connections with three distinct scientific disciplines: chemistry, physics, and biology.